2011
DOI: 10.1038/sj.bdj.2011.768
|View full text |Cite
|
Sign up to set email alerts
|

General dental practitioners' knowledge of polymerisation of resin-based composite restorations and light curing unit technology

Abstract: at the wrong wavelengths, are inadequately polymerised. 9,10 Conversion is seldom complete 11-14 and lower conversion results in reduced physical properties, 16-20 reduced bond strengths, 20 decreased marginal integrity and increased wear, 21,22 higher permeability, 23 more water sorption 24 and more leaching out of uncured monomers. 25,26

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 37 publications
1
32
0
2
Order By: Relevance
“…Similarly, previous studies also verifed that the majority of dentists were not aware that the light curing units require periodic testing and maintenance 15,25 . While for LED units the need for energy monitoring is less required, since LED units are able to keep the irradiance stable for long time, for QTH units these monitoring should be mandatory and weekly performed 15,20,25 . …”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Similarly, previous studies also verifed that the majority of dentists were not aware that the light curing units require periodic testing and maintenance 15,25 . While for LED units the need for energy monitoring is less required, since LED units are able to keep the irradiance stable for long time, for QTH units these monitoring should be mandatory and weekly performed 15,20,25 . …”
Section: Discussionmentioning
confidence: 68%
“…Quartz-tungsten halogen (QTH) lights used to be the preferred method of composite activation, but light-emitting diode (LED) units have gained popularity in the market and in clinical practice 15,16 , and currently LEDs have demonstrated deeper polymerization capacity, higher lamp lifespan, and lower heat generation 12,23 . In addition, while QTH light units require constant monitoring, in LED units such routine monitoring is not mandatory 15,25 . …”
Section: Introductionmentioning
confidence: 99%
“…Ein besseres Verständnis der mit der Lichtpolymerisation verbundenen Vorgänge hilft nicht nur dabei, LED-FPL in der Zahnarztpraxis besser einzusetzen, sondern es lässt uns auch staunen. Wie eine Studie aus Großbritannien kürzlich gezeigt hat, ist das Wissen vieler Zahnärzte über die Fotopolymerisation dentaler Materialien erstaunlich gering [2]. Dieser Artikel fasst zentrale Fakten zum Thema LED-FPL für den Praktiker kompakt zusammen.…”
Section: Cme-fortbildungunclassified
“…This is supported by the results of surveys of general dentists' knowledge of polymerization of RBC and light-curing technology that revealed that there is a need for further education and guidance in this aspect of primary dental care. 38,39 On the basis of advertising claims alone, most practitioners recognize that not all new LCUs are equivalent, and this observation is supported by the literature. 18,[40][41][42][43][44][45][46][47][48][49] Investigators in several studies have evaluated the light intensity from LCUs used in dental offices.…”
mentioning
confidence: 94%
“…The authors of several articles have questioned the adequacy of instruction in how to deliver a sufficient amount of energy from a curing light to a restoration to cure the RBC properly. 15,18,38,39 We have used the patient simulator in many continuing dental education courses to evaluate general dentists' light-curing techniques and to educate them regarding how to deliver an adequate amount of energy to cure their RBC restorations. During these courses and when conducting other studies, we found that there was a wide range in the abilities of dentists and DS to use their curing lights.…”
mentioning
confidence: 99%